2016
DOI: 10.3389/fpls.2016.01295
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Inducible Expression of an F-box Gene TaFBA1 from Wheat Enhanced the Drought Tolerance in Transgenic Tobacco Plants without Impacting Growth and Development

Abstract: E3 ligase plays an important role in the response to many environment stresses in plants. In our previous study, constitutive overexpression of an F-box protein gene TaFBA1 driven by 35S promoter improved the drought tolerance in transgenic tobacco plants, but the growth and development in transgenic plants was altered in normal conditions. In this study, we used stress-inducible promoter RD29A instead of 35S promoter, as a results, the stress-inducible transgenic tobacco plants exhibit a similar phenotype wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…The results showed that this spraying rate had little influence on Microcoleus vaginatus and was suitable for their growth and amplification. Research found that low MDA content indicated that plants were under less stress, and high MDA content indicated more serious oxidative damage to the plant cell membrane [22,23], which was consistent with our results. Soluble protein makes up various antioxidant enzymes, and changes in their content reflect protein synthesis and the degradation of various information in the cell.…”
Section: Resultssupporting
confidence: 90%
“…The results showed that this spraying rate had little influence on Microcoleus vaginatus and was suitable for their growth and amplification. Research found that low MDA content indicated that plants were under less stress, and high MDA content indicated more serious oxidative damage to the plant cell membrane [22,23], which was consistent with our results. Soluble protein makes up various antioxidant enzymes, and changes in their content reflect protein synthesis and the degradation of various information in the cell.…”
Section: Resultssupporting
confidence: 90%
“…Our previous studies showed that the wheat F-box gene TaFBA1 is involved in plant stress tolerance. It was shown that TaFBA1 overexpression improves drought, salt, and high-temperature stress tolerance of transgenic tobacco plants (Kong et al, 2016; Zhao et al, 2017; Li et al, 2018). We also observed that ABA could induce expression of the TaFBA1 gene in wheat (Zhou et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We studied the functions of TaFBA1 in plant growth and stress tolerance by overexpressing it in tobacco. Study results showed that overexpression of TaFBA1 improves drought, salt, heat, and oxidative stress tolerance in transgenic tobacco plants (Zhou et al, 2014; Zhou et al, 2015; Kong et al, 2016; Zhao et al, 2017; Li et al, 2018). Results also showed that seed germination in transgenic tobacco that overexpresses TaFBA1 is less sensitive to ABA; stoma movement of TaFBA1-overexpressing tobacco was also insensitive to drought stress in our laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our findings indicated that the ectopic expression of GmRR34 resulted in retarded growth in the transgenic plants under normal growth conditions ( Figure 1B-D). Previous studies also reported on similar phenotypic alteration in relation to improved drought tolerance/resistance when using constitutive 35S promoter to drive the expression of transgenes in various transgenic species, including Arabidopsis [40][41][42], tobacco [43,44], and tomato [45,46].…”
Section: Discussionmentioning
confidence: 64%